2020
DOI: 10.1177/2325967120930660
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies in the MRI Evaluation of Supraspinatus Volume After Repair

Abstract: Background: Reversibility of rotator cuff atrophy after surgical repair is controversial. Traditionally, the cross-sectional area (CSA) of the rotator cuff was measured in conventional Y-view (CYV) via magnetic resonance imaging (MRI) to evaluate reversibility. However, it has been suggested that scanning axis inconsistency in CYV was overlooked and that the CSA in CYV reflects not only atrophy but also rotator cuff retraction. Hypothesis: Discrepancies between scanning axes in CYV cause significant errors whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…However, these reports of reversibility are currently attracting more scrutiny. The primary controversy involves the lateralization of the myotendinous unit after repair, which can immediately result in an immediate increase in the supraspinatus occupation ratio, even though the muscle volume is unchanged, by altering the assessment plane 3,18,19,33 . Some authors have used images made immediately after surgery as a baseline to overcome this drawback, but these studies have still reported contradictory results 3,6,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these reports of reversibility are currently attracting more scrutiny. The primary controversy involves the lateralization of the myotendinous unit after repair, which can immediately result in an immediate increase in the supraspinatus occupation ratio, even though the muscle volume is unchanged, by altering the assessment plane 3,18,19,33 . Some authors have used images made immediately after surgery as a baseline to overcome this drawback, but these studies have still reported contradictory results 3,6,34 .…”
Section: Discussionmentioning
confidence: 99%
“…the Y-view plane for radiographic measurements could be one of the main explanations, as data from a single slice fail to represent the actual 3D volume 9,33 .…”
mentioning
confidence: 99%
“…Additionally, using the scapular Y view of MRI to evaluate supraspinatus CSA and occupation ratio has its own unique limitations with regard to inconsistencies in scanning axis of the reconstructed image. 10 Furthermore, there is an inability to perform volumetric analysis of muscle atrophy on standard shoulder MRI owing to the limited field of view, which does not include the entire muscle belly of the supraspinatus. Despite this, the methodology used in our study, including occupation ratio, supraspinatus CSA, and tangent sign, is consistent with the current standard for evaluating atrophy in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…3,[18][19][20]22 However, there is concern that 2-dimensional assessment of the supraspinatus muscle on cross-sectional imaging may not be an accurate representation of the true atrophy of the muscle fibers of the rotator cuff. 4,10,21 Specifically, rotator cuff tendon retraction has been shown to falsely overestimate muscle atrophy appreciated on MRI, 4,21 which can have clinically significant implications for determining the repairability and functional prognosis after rotator cuff repair. Although MRI is a clinically useful noninvasive method of assessing muscle atrophy, muscle biopsy has been performed to directly measure myofiber cross-sectional area (CSA) histologically.…”
mentioning
confidence: 99%
See 1 more Smart Citation